IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT THROUGH FOCUS GROUP DISCUSSION ( FGD ) - Wenny Sasmita; Busmin Gurning (Universitas Negeri Medan, 2012)
This study deals with the improvement of students’ writing achievement through focus group discussion method. The objective of this study is to find out whether students’ writing achievement will be improved through focus group discussion method. This study was conducted by using classroom action research. The subject of this research was class VIII-4 SMPN. 2 Tanjung Pura. The number of the students was 36 students which consist of 18 male students and 18 female students. The research was conducted in two cycles. Each cycle consisted three meetings. The instrument for collecting the data were quantitative data (writing test ) and qualitative data ( observation sheet, interview and field note). Based on the analysis, students’ achievement kept improving in every test. Key Words : Writing, Recount, Focus Group Discussion